EFFECT OF GIVING EARTHWORMS WITH DIFFERENT FREQUENCY ON GROWTH AND SURVIVAL RATE OF KOI (Cyprinus carpio) LARVAE - Harlyanto Harlyanto; Nuraini Nuraini; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Email : Harlianto@gmail.comABSTRACKThis research was conducted in 28 January – 8 March 2019 at Fish Breeding Laboratory of Fisheries and Marine Faculty, University of Riau. This study aims to see the effect of giving earthworms with different frequencies to growth rate and survival rate of koi fish larvae. The method used in this study is the experimental method using a completely factor randomized design (CRD) and four treatments with three replications. The treatments applied in this study are: P3 = Giving earthworms 3 times a day at 08:00 am, 4:00 pm and 00:00 am,P4 = Giving earthworms 4 times a day at 08:00 am, 02:00 pm, 08:00 pm and 02:00 am, P5 = Giving earthworms 5 times a day at 08:00 am, 01:00 pm, 06:00 pm, 01:00 am and 06:00 am, P6 = Giving earthworms 6 times a day at 08:00 am, 12:00 pm, 04:00 pm, 08:00 pm, 00:00 am and 04:00 am. The results showed that the best frequencies of giving earthworms koilarvae are P3, with absolute weight growth 0,53 g, specific growth rates 6,62 %, absolute length growth 2,89 cm, and survival rate 80%. Temperatures range from 26-29oC, pH 6.4-7.1 and Dissolved Oxygen 4.2-5.2 mg/L. The value of this water quality has been with the standard of maintenance of koi fish.Keywords: Feed frequency, Larvae, Koi fish, Growth.